Analysis of sediment transport in sewer pipes using a coupled CFD-DEM model and experimental work. Issue 4 (21st April 2019) - Alihosseini, Maryam; Thamsen, Paul Uwe
ABSTRACT: The present work aims to experimentally and numerically study the self-cleansing velocity for non-cohesive sediments in urban sewers as well as the influence of the particle size and bed roughness on the sediment transport. Experiments were conducted in a circular laboratory pipe using sand and gravel over smooth and rough beds. The results were used to validate three-dimensional simulations performed with a coupled computational fluid dynamics (CFD) model and discrete element method (DEM). The CFD part of the simulation was carried out in ANSYS Fluent, which is two-way coupled to the DEM software EDEM. Results have shown that sediment size has a greater effect on critical velocity than bed roughness, while sediment velocity is strongly dependant on the bed roughness. Good correspondence between numerical and experimental results indicated that a CFD-DEM model could be a good tool for an analysis of sediment transport.